2021
DOI: 10.1186/s12885-020-07758-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiangiogenic-based treatment and systemic inflammatory factors on outcomes in patients with BRAF v600-mutated metastatic colorectal cancer: a real-world study in Spain

Abstract: Background Outcomes are poorer in metastatic colorectal cancer (mCRC) patients with BRAF V600E mutations than those without it, but the effect of these mutations on treatment response is unclear. This real-world study assessed the effects of antiangiogenic-based treatment and systemic inflammatory factors on outcomes in patients with BRAF V600-mutated mCRC. Methods This real-world, multicenter, retrospective, observational study included patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In terms of prognosis, a multicenter RWS found that antiangiogenic-based regimens prolonged median PFS in patients with mCRC, while the systemic inflammation score, neutrophil–lymphocyte ratio (NLR) and serum albumin could predict the efficacy of treatment [ 79 ]. In addition, the study also confirmed that patients with BRAF mutations responded poorly to treatment than wild-type (WT) BRAF tumors, resulting in a worse prognosis [ 79 ]. A retrospective study also confirmed that in mCRC patients, WT patients have higher OS [ 80 ].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…In terms of prognosis, a multicenter RWS found that antiangiogenic-based regimens prolonged median PFS in patients with mCRC, while the systemic inflammation score, neutrophil–lymphocyte ratio (NLR) and serum albumin could predict the efficacy of treatment [ 79 ]. In addition, the study also confirmed that patients with BRAF mutations responded poorly to treatment than wild-type (WT) BRAF tumors, resulting in a worse prognosis [ 79 ]. A retrospective study also confirmed that in mCRC patients, WT patients have higher OS [ 80 ].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…[20][21][22] The preoperative SIS was shown to be an effective prognostic factor in many cancers. 19,[23][24][25][26] However, studies on the ability of the SIS system to predict the survival of PCa patients have not been reported. Thus, in this study, we elucidated the prognostic effect of the pretherapeutic SIS in patients with PCa in a Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…24 Galizia et al suggested that the SIS system was not associated with the survival of CRC patients in a multivariate analysis. 27 In addition, two studies 25,26 utilized a modified SIS system with 19 However, those studies obtained conflicting results regarding OS. 25,26 Martínez-Lago et al showed that the SIS was a prognostic factor for OS, 26 while Wang et al found that the SIS was not associated with the survival of CRC.…”
mentioning
confidence: 99%
See 2 more Smart Citations